(untitled) (Педагогіка вищої та середньої школи, 2022)
The article deals with the conception of readiness for different kinds of activities and professional oriented training. The conditions which will have a positive influence on forming of prospective teacher readiness for professional oriented training of senior pupils are submitted for consideration.